Rache verkünden - Flebbe, Jochen (Pastoraltheologie, 2017)
Reprint of a sermon on the topic "Are Psalms of Revenge Acceptable?", given at a University Protestant Church service in Bonn, as part of a series of sermons under the title "Psalms - Variations".